Serological evidence of hepatitis A, B, and C virus infection in older adults in Khon Kaen, Thailand and the estimated rates of chronic hepatitis B and C virus infection in Thais, 2017 - Posuwan,Nawarat; Vuthitanachot,Viboonsak; Chinchai,Teeraporn; Wasitthankasem,Rujipat; Wanlapakorn,Nasamon; Poovorawan,Yong (PeerJ, 2019)
Hepatitis A (HAV), hepatitis B (HBV), and hepatitis C (HCV) viruses are hepatotropic viruses responsible for acute/chronic hepatitis associated with liver failure, cirrhosis, and hepatocellular carcinoma. Due to the limited data on the prevalence of hepatitis in the older population in Thailand, this study aimed to evaluate the seroprevalence of these viruses in elderly Thais. Using an automated immunoassay, serum samples from individuals older than 60 years of age in Chum Phae district of Khon Kaen province in northeast Thailand were analyzed for anti-HAV (n = 93), HBV markers (n = 460, HBsAg, anti-HBs, and anti-HBc), and anti-HCV (n = 460). Samples were classified into five age groups (61–65, 66–70, 71–75, 76–80, and >80 years). The overall seroprevalence of anti-HAV, HBsAg, anti-HBc, anti-HBs, and anti-HCV was 98.9%, 4.6%, 51.5%, 32.4%, and 1.3%, respectively. When samples were stratified into three groups representing three generations (children/young adults aged 6 months-30 years and middle-aged adults between 31–60 years old from a previous survey, and older adults aged >60 years from the current study), the highest levels of anti-HAV and anti-HBc were found in older adults. Children/young adults had the lowest levels of HBsAg and anti-HCV, and the highest level of anti-HBs. These findings are consistent with the integration of HBV vaccination into the Expanded Program on Immunization (EPI) in 1992 and coincide with increased awareness of blood-borne viral transmission in Thailand. Extrapolating from our data, the estimated numbers of cases of chronic HBV and HCV infection in Thailand in 2017 were 2.2 and 0.79 million, respectively. Thus, effective treatments for viral hepatitis B and C for middle-aged and elderly Thais are needed. This seroprevalence survey could be used to help formulate policies and possible guidelines for treatment and prevention in specific age groups, which is recommended to facilitate the elimination of viral hepatitis by 2030.
Keywords: Viral hepatitis; Older adult; Thailand